Slot-predicting based ALOHA algorithm for RFID anti-collision - LI Meng; QIAN Zhi-hong; ZHANG Xu; WANG Yi-jun (Tongxin xuebao)
The proposed algorithm modified the prior frame size by comparison with the preset decision threshold and identified the end conditions based on the value of accumulation factor C of EPC protocol.The slot-predicting binary se-lection scheme was used in each frame to accelerate idle slots and solve collisions with binary selection instantly,so that to reduce the invalid slots.Simulation results show that the proposed algorithm can increase the system throughput and consumes less power and fewer time slots than previous work,and provide a solution for data collection of Internet of Things which takes RFID tags as perceptive terminal nodes.